Iowa RBA, October 6, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for October 6, 1997. Highlights of the update include the continued presence of Eurasian Collared Doves and a Red Crossbill sighting. Also of interest were sightings of several noticeable migrants, including Franklin's Gull, Golden-crowned Kinglet, Yellow-rumped Warbler, and Winter Wren. Also included are handwritten notes for the next week's update with sightings of a Lesser Black-backed Gull, a White-faced Ibis, and a juvenile Sabine's Gull. Epson - sheet feed/flatbed